THE EFFECT OF RESPIRATORY PHYSIOTHERAPY ON ATELECTASIS AND OXYGENATION IN POST-CARDIAC SURGERY PATIENTS - YOUSAF, B; HUSSAIN, AS; RAFIQ, K; SARWAR, R; LATIF, S; AYUB, Z (Biological and Clinical Sciences Research Journal, 2024)
Post-operative pulmonary complications, particularly atelectasis, are common following cardiac surgery, contributing to prolonged recovery and increased morbidity. This study evaluates the effect of respiratory physiotherapy on atelectasis resolution and oxygenation in post-cardiac surgery patients in Pakistan. Methods: A prospective observational study was conducted at Sheikh Zayed Hospital, Lahore, from March to July 2024, involving 80 patients divided equally into an intervention group and a control group. The intervention group received standard care with respiratory physiotherapy, including deep breathing exercises, incentive spirometry, and early mobilization, while the control group received standard care alone. Primary outcomes included atelectasis resolution assessed via chest X-rays and oxygenation measured through arterial blood gas analysis. Secondary outcomes included pulmonary infection rates, ICU stay duration, and total hospital stay. Results: The intervention group demonstrated significantly improved atelectasis resolution scores by postoperative day 5 (1.3 ± 0.5 vs. 2.6 ± 0.8, p < 0.001) and enhanced oxygenation levels (PaO2: 96.2 ± 7.3 vs. 86.9 ± 8.5 mmHg, p < 0.001) compared to the control group. Pulmonary infections were significantly lower in the intervention group (12.5% vs. 30%, p < 0.05), and ICU and hospital stays were reduced (ICU stay: 3.4 ± 1.1 vs. 4.9 ± 1.6 days, p < 0.001; hospital stay: 7.1 ± 2.2 vs. 9.3 ± 2.4 days, p < 0.001). Conclusion: Respiratory physiotherapy effectively improves atelectasis resolution, oxygenation, and recovery outcomes in post-cardiac surgery patients. Incorporating structured physiotherapy into routine care is essential for optimizing outcomes, particularly in resource-constrained settings like Pakistan.